Magnetic Resonance Imaging-Guided Biopsy in Active Surveillance of Prostate Cancer. Issue 4 (2nd April 2022) - Kinnaird, Adam; Yerram, Nitin K.; O'Connor, Luke; Brisbane, Wayne; Sharma, Vidit; Chuang, Ryan; Jayadevan, Rajiv; Ahdoot, Michael; Daneshvar, Michael; Priester, Alan; Delfin, Merdie; Tran, Elizabeth; et al.
Abstract : Purpose: The underlying premise of prostate cancer active surveillance (AS) is that cancers likely to metastasize will be recognized and eliminated before cancer-related disease can ensue. Our study was designed to determine the prostate cancer upgrading rate when biopsy guided by magnetic resonance imaging (MRGBx) is used before entry and during AS. Materials and Methods: The cohort included 519 men with low- or intermediate-risk prostate cancer who enrolled in prospective studies (NCT00949819 and NCT00102544) between February 2008 and February 2020. Subjects were preliminarily diagnosed with Gleason Grade Group (GG) 1 cancer; AS began when subsequent MRGBx confirmed GG1 or GG2. Participants underwent confirmatory MRGBx (targeted and systematic) followed by surveillance MRGBx approximately every 12 to 24 months. The primary outcome was tumor upgrading to ≥GG3. Results: Upgrading to ≥GG3 was found in 92 men after a median followup of 4.8 years (IQR 3.1–6.5) after confirmatory MRGBx. Upgrade-free probability after 5 years was 0.85 (95% CI 0.81–0.88). Cancer detected in a magnetic resonance imaging lesion at confirmatory MRGBx increased risk of subsequent upgrading during AS (HR 2.8; 95% CI 1.3–6.0), as did presence of GG2 (HR 2.9; 95% CI 1.1–8.2) In men who upgraded ≥GG3 during AS, upgrading was detected by targeted cores only in 27%, systematic cores only in 25% and both in 47%. In 63 men undergoing prostatectomy, upgrading from MRGBx was found in only 5 (8%). Conclusions: When AS begins and follows with MRGBx (targeted and systematic), upgrading rate (≥GG3) is greater when tumor is initially present within a magnetic resonance imaging lesion or when pathology is GG2 than when these features are absent.